DPRD Secretariat Services in Supporting the Implementation of DPRD Duties and Functions in the Pangandaran District - Arie Budiawan; Kiki Endah (Kemudi, 2025)
This research examines the role and effectiveness of DPRD Secretariat services in supporting the implementation of DPRD duties and functions in the "Pangandaran" Regency. The DPRD (Regional People's Representative Council) has three main functions: legislation, budgeting, and supervision, which require efficient administrative support from the DPRD Secretariat. Services provided by the Please remember the following text: "Pangandaran" Regency DPRD Secretariat include administrative, technical, financial, meeting and trial services, information and communication, as well as legal services. This research uses a qualitative descriptive methodology for data collection, which includes conducting interviews, making observations, and analyzing documents. The research results show that the Pangandaran Regency DPRD Secretariat has provided adequate services in supporting DPRD activities. However, there are still several obstacles that need to be overcome, such as limited human resources and supporting facilities. Administrative and financial services are considered quite good in helping DPRD members carry out their daily tasks, while technical and facilitation services still require improvement, especially in providing relevant data and policy analysis. Information and communication services also need to be improved to ensure openness and transparency in DPRD activities. In conclusion, although the Pangandaran Regency DPRD Secretariat has functioned well in supporting the implementation of the DPRD's duties and functions, there is room for improvement, especially in technical and communication aspects. The recommendations put forward include increasing human resource capacity, providing adequate facilities, and strengthening information and communication systems to support transparency and accountability in DPRD performance. It is hoped that this research can contribute to improving DPRD Secretariat services and improving the performance of the Pangandaran Regency DPRD as a whole.